EYE-R : Augmented Reality as Mobile Based Helper Application for Colorblinds - Irfansyah, Naufal Herma; Kurniawan, Rahadian (Politeknik Ganesha Medan, 2024)
The ability to identify color is a basic ability for a human to live easily. Unfortunately not all humans have normal sight, there are some humans who have an eye disorder called color blindness. Color blindness is an eye disorder that affects color perception of the affected person in everyday life, therefore the person that has color blindness needs a device to help them to identify some colors. In the medical world, the usage of Augmented Reality is still limited for education for medical practitioners, so the application of AR as a tool to help patients is still considered to be minimal. Augmented Reality as a Mobile Based Colorblind Helper Research aims to find out how effective a color detection system using AR as a tool to help the colorblinds identify color in an application called “EYE-R”. The research method employed in the research and development of this application is the Waterfall method that involves the stages of Requirements, Design, Programming, Testing, and Implementation. The main feature of “EYE-R” is chosen using a survey which is Real Time Color Detection which is developed using the Unity engine and implemented using Android. The research results show that the majority of users can operate the Real Time Color Detection system accurately. The user satisfaction results recorded using USE Questionnaire shows that the EYE-R Real Time Color Detection system really helps users’ daily lives and can be used very well.